A prodigal paradigm for the solution of issues and challenges which leads in Big data security - et. al., Himani Sivaraman, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Recent technological development such as social network, cloud computing, and data analytics make possible to collect large amount of data. Data security and privacy are critical aspects of concern. However , there are issues in securing and protecting this data.Big data is like a two edged sword, as it bring convenience of handling the huge amount of data along with it creates certain risks for the analysts. It is believed in the process of data collection , storage, manipulation, presentation, the data leak- age can exists as unavoidable ghost. The big data architecture being distributive in nature, undergo portioning , replication and distribution of this data on thousands of data processing nodes for the distribution of this .How to make the data security and privacy more significantly strong and to stop the data leakage in the stages of the dif- ferent algorithm has become a essential goal and most important research challenge for researchers and academicians. This paper discusses and review the issues and the key factors what is to be taken in account while undergoing development of secured big data solutions. It can increase the performance of impact and resultant solutions for these crisis. The traditional methods of privacy cannot be that much successful in providing solution to this arising situation.